Assessing the quality of participation in farmers' research groups in the Highlands of Kabale, Uganda - Sanginga, Pascal C.; Lilja, Nina; Tumwine, Jackson K. (International Center for Tropical Agriculture, 2001)
In recent years, there has been increasing interest in farmer research groups (FRG) to catalyse farmer participation in research, and to widen the impact of participatory research. However, there is dearth of systematic empirical studies that evaluates the quality of participation in FRG. Using empirical data from a sample of 21 FRGs in Kabale, Uganda, this paper investigates what types of participatory research occurred at the different stages of the research process, how farmer participation occurred, who participates in FRG, what are the factors that determined farmers' participation in FRG, and what criteria should be used in monitoring and evaluating the performance of FRG. Results showed that the types of participation were more of functional consultative and collaborative types, but varied in the different stages of the research process as farmers were increasingly taking on more roles and responsibilities. Results showed that farmer participation in FRG tend to follow a "U" shaped curve, with high participation at the initial stages of the process, followed by dramatic decrease as many farmers drop out from the groups, and slow increases towards the end of the first seasons. Similarly, there was a significantly higher participation of male farmers at the beginning of the process, compared to women. However, as FRGs progressed, the proportion of men decreased while the relative proportion of women increased dramatically to reach about 67% of farmers in mixed groups, and 24% of the FRGs were women only. These results suggest that FRG proved to be a more effective mechanism to involve women and the resource-poor farmers in research who would otherwise be bypassed by conventional approaches. The results of the Logit regression model confirmed that the probability of participating in FRG was higher for women compared to men, and that there were no significant differences in wealth circumstances between FRG members and the rest of the community. We argue that FRG as an approach has a great potential for catalyzing the participation of farmers as partners in research and development activities. However, this requires significant support and personal commitment of researchers to broaden the scope of FRGs from a functional consultative type to a more collegial empowering type, and from variety evaluation to broader natural resources management research and other developmental issues.